Quantitative value chain approaches for animal health and food safety - Rich, Karl M.; Dizyee, K.; Huyen Nguyen, Thi-Thu; Ha Duong, N.; Hung Pham Van; Nga Nguyen Thi Duong; Unger, Fred; Lapar, Ma. Lucila (Elsevier, 2018)
Economic impact assessments are increasingly important in the context of animal health and food safety, although much of the existing literature does not address the broader systems context in which disease transmission takes place. In this paper, we discuss the role of system dynamics modeling in addressing the value chain impacts associated with animal health and food safety issues. System dynamics methods hold promise as a means of capturing the complex feedbacks that exist between the biology, economics, and behavioral aspects of food safety and animal health systems. We provide a proof-of-concept of this approach in the context of food safety and animal health in the smallholder pig sector of Viet Nam. Results highlight the important tradeoffs that exist between policy objectives and the costs required to achieve them.